OPTIMALISI KEMAMPUAN GURU PENDIDIKAN JASMANI SMA MATERI PENCAK SILAT MELALUI PELATIHAN TEORI DAN PRAKTEK - Adi Sumarsono; Afif Khoirul Hidayat; Landy Eko S Ramadona (Musamus University, 2019)
The background for this activity is from physical education teachers in high schools in Merauke Regency. The purpose of this Community Service activity is to optimize the pencak silat material that has been taught to school students aside from extra-curricular material. The method used in the implementation of this activity was the provision of material which was continued by direct practice in the field. The result of this PKM activity is the achievement of service objectives measured from the orientation of understanding, knowledge and direct practice in the form of motion experience from the participants of the activity. In addition to providing knowledge and practice, the participants were also given learning material to start making the Pencak Silat RPP, to teach and assess the results of the martial arts learning.